2014
DOI: 10.1007/s11605-013-2377-0
|View full text |Cite
|
Sign up to set email alerts
|

Internal Hernia After Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Closure of mesenteric defects and ante-colic Roux limb position result in a significantly lower IH rate. Furthermore, a high index of suspicion must be maintained since symptoms may be nonspecific and imaging may be negative in nearly 20 % of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
3
30
0
3
Order By: Relevance
“…The false negative rate of CT in our study is consistent with previous reports that show a false negative rate of 13.5-17.8 % [11,32]. The mesenteric swirl sign was the most common CT finding in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…The false negative rate of CT in our study is consistent with previous reports that show a false negative rate of 13.5-17.8 % [11,32]. The mesenteric swirl sign was the most common CT finding in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…A Petersen herniation was seen in half of those with an internal herniation in this study (22 of 42). In older studies, jejunojejunostomy hernias occurred more frequently than Petersen hernias, whereas more recent studies found more Petersen hernias, with rates ranging from 40·5 to 75 per cent. Defects were found to be equally distributed over the two sites in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Geubbels and colleagues 5 reported that cramping or colic pain was the most common symptom in patients with internal herniation. Abdominal pain, nausea or vomiting were the most common complaints in several previous studies 3,4,7,11,12 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The number of patients included in studies (6)(7)(8) in which authors evaluated the CT signs associated with IH is relatively low (typically fewer than 20 patients per study). In addition, up to 20% of patients with IH may have CT findings negative for IH (9,10). Furthermore, diagnosis of IH with CT shows considerable interobserver variability, with wide ranges of reported diagnostic accuracy.…”
Section: Patientsmentioning
confidence: 99%